(untitled) (Heritage, 2020)
Abstract: Lola Montes (Marie Dolores Eliza Rosanna Gilbert) is a dominant heroin of Todor Manojlović’s drama Fascinated king: historical movie in seven pictures with intermezzo. Manojlović is one of the many writers who have dedicated a piece to the fatal Lola Montes, whose dance adorned stages of the European cities. Having a great faith on authentic historical data, our playwright has created a drama portrait of the Spanish dancer who seduced Bavarian king Ludwig I and became his mistress and the very important political figure. It has been shown, on adequate examples, that the game and adventure are, without a doubt, the essential components of the Manojlović’s drama character. Special research attention is given to the symbol of Lola’s Spanish dance. Manojlović’s Lola Montes is seductive, with great temper, coquettish, cunning, stunning young woman, the bearer of the new political ideas and a cause of many confrontations. The aged and fascinated king Ludwig I gives this woman a palace, title of countess and eventually he is forced to abdicate. The very important segment of this paper is given to the precise analysis of the scene where Lola Montes and king Ludwig are completely ignore the reality and leave their minds to the fairy-tale game and enjoy in the imaginary roles. The way of Todor Manojlović portraying the femme fatale has also been analyzed.